Imagination house : an entrepreneurial life - Walker, E. Lee, 1941- (Texas A & M University Press, 2019)
When twenty-one-year-old Michael Dell asked E. Lee Walker to be the president of his fledgling computer company, PC?s Limited, Walker, in his mid-forties, immediately thought about all the people who had helped him through life?as an undergraduate at Texas A&M (class of ?63), a graduate student at Harvard, and a once-young entrepreneur himself. As he and Dell created the foundation of what would become one of the most successful companies in the world, Walker was guided by the lessons of his past business ventures, by his belief in the power of imagination, and by his relationships with people who had provided encouragement when he most needed it. When he left Dell Computer Corporation to teach, Walker discovered that the stories he took with him?of his aspirations, of his failures and triumphs, and of his friends and mentors?were the key to engaging and inspiring his students. Here, Walker records those stories in a memoir that spans five decades and reveals a man whose curiosity, resourcefulness, and luck led him out of South Texas and into corporate boardrooms, university lecture halls, and community activism. In fast-paced tales about life as a high-tech entrepreneur, adjunct professor, civic leader, and environmental advocate, Walker manages to convey the importance of creative thinking and communal effort in all his endeavors. Originally offered to a small group of college students in Italy for study abroad, this affecting memoir will introduce to a wider audience not only a seasoned executive and philanthropist but also a wise and delightful storyteller.